Nigeriens say cheese - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Some 100 farmers in Niger are recently producing cheese from dromedary milk with the assistance of Karkara, a local NGO. Cheese making with this milk is difficult since it does not easily coagulate. A combination of low levels of certain enzymes and...